Perancangan Sistem Penjualan Tiket pada Tour Travel XYZ - Hafid Dwi Adha; Lova Endriani Zen (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2025)
Recently, technology is developing at a very quick pace, and competition is becoming more fierce. Undoubtedly, advancements in technology are also related to computers. The ability to communicate is something that every human being on the planet needs. This is due to the fact that the advantages are significantly higher than those of other tool components. Additionally, computers can deliver precise and timely information. There is now a dearth of information from Tour Travel XYZ, a company in the tourism industry, about both available tourist sites and ticket reservations as well as information on tourism services like tours and travel. The goal of this design is to develop a website that will facilitate ticket promotion for Tour Travel XYZ managers and leaders, boost sales and competitiveness by putting in place a web-based sales information system, facilitate ticket purchases for current and potential customers so they don't have to visit the office in person, and expand the ticket sales network at Tour Travel XYZ.